2013
DOI: 10.1103/physrevb.88.094505
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of electronic and magnetic properties in Fe1+y(Te1xSeet al.

Abstract: We have studied the coupling of electronic and magnetic properties in Fe1+y(Te1-xSex) via systematic specific heat, magnetoresistivity, and Hall coefficient measurements on two groups of samples with y = 0.02 and 0.1. In the y = 0.02 series, we find that the 0.09 < x < 0.3 composition region, where superconductivity is suppressed, has large

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
79
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(84 citation statements)
references
References 59 publications
(115 reference statements)
5
79
0
Order By: Relevance
“…In others, the two phases coexist in a narrow composition range where the long-range magnetic ordering takes place at temperatures above the superconducting transition [16][17][18]. In iron chalcogenides, on the other hand, an intermediate composition regime exists with short-range magnetic ordering which is characterized by charge carrier localization [19][20][21]. The crossing-over from (π, 0) (defined in the crystallographic Fe 1+y Te lattice) long range order in Fe 1+y Te into a (π, π) magnetic resonance in substituted superconducting Fe 1+y Te 1−x Se x reinforces the view that an intermediate composition regime exists within which short-range magnetic order and superconductivity compete [20,22,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In others, the two phases coexist in a narrow composition range where the long-range magnetic ordering takes place at temperatures above the superconducting transition [16][17][18]. In iron chalcogenides, on the other hand, an intermediate composition regime exists with short-range magnetic ordering which is characterized by charge carrier localization [19][20][21]. The crossing-over from (π, 0) (defined in the crystallographic Fe 1+y Te lattice) long range order in Fe 1+y Te into a (π, π) magnetic resonance in substituted superconducting Fe 1+y Te 1−x Se x reinforces the view that an intermediate composition regime exists within which short-range magnetic order and superconductivity compete [20,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Inelastic neutron scattering studies on superconducting and non-superconducting Fe 1+y Te 1−x Se x also revealed spin fluctuations dominated by incommensurate excitations [25,26]. The suppression of long range magnetic order and the emergence of a superconducting transition with increase in Se composition have been investigated by various groups [11,19,21,27,28]. The temperature composition phase diagram exhibits three regions, as Se composition increased up to 50%: commensurate AFM order followed by a region where incommensurate AFM order and superconductivity coexist, and bulk superconductivity [19].…”
Section: Introductionmentioning
confidence: 99%
“…The (,0) magnetic correlations are found to cause incoherent magnetic scattering, which is detrimental to superconductivity 20 . As a result, the superconductivity in Fe(Te 1-x Se x ) occurs only when the (,0) magnetism is greatly suppressed by much higher concentration of Se, e.g., x>0.29 19,20 .…”
mentioning
confidence: 99%
“…The (,0) magnetic correlations are found to cause incoherent magnetic scattering, which is detrimental to superconductivity 20 . As a result, the superconductivity in Fe(Te 1-x Se x ) occurs only when the (,0) magnetism is greatly suppressed by much higher concentration of Se, e.g., x>0.29 19,20 . Although earlier experiments highlighted the "coexistence" of superconductivity and magnetic order in low Se concentration samples [21][22][23] , it has been later clarified that the "superconductivity" observed in this region is only a trace, which cannot be probed by bulk property measurements such as specific heat 19,20,24 .…”
mentioning
confidence: 99%
See 1 more Smart Citation